Literature Study in Numeracy Learning for Children with Special Needs and Policy Alternatives - Asrori, Muhammad Abdul Roziq; Mahardhani, Ardhana Januar; Wahyudi, Wahyudi; Nurhidayah, Dwi Avita (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
Conditions in the field show that children with special needs who are blind and slow learners still have many deficiencies in math problems. Therefore, there needs to be an in-depth discussion on this matter. This article will describe the process of teaching and learning arithmetic for students with special needs through article analysis so that later it will be known how to ideally carry out numeracy learning for children with special needs through a policy. This research aims to describe the counting process of teaching and learning of students with special needs. This study uses a systematic literature review method. Data collection was carried out by documenting and reviewing previous articles related to the process of learning numeracy for students with special needs. Articles are searched by searching for articles using the Google Scholar database. Included in the discussion of this learning process are learning methods and models, learning media, and difficulties or challenges faced by students with special needs and teachers in learning numeracy. The final results of the review can be concluded that the process of teaching and learning numeracy between regular students and students with special needs has several differences, including the number of students, the time of delivery of material, and teaching and learning activities. Four alternative policies are proposed: facilitating accompanying teachers, preparing disability-friendly school facilities, collaborating with institutions dealing with children with special needs, and preparing numeracy media.